1983
DOI: 10.1119/1.13226
|View full text |Cite
|
Sign up to set email alerts
|

Potential difference and current in simple electric circuits: A study of students’ concepts

Abstract: A study which was designed to identify students’ concepts of simple electric circuits is reported. A diagnostic questionnaire was administered to a sample of 145 high school students and 21 physics teachers. The questionnaire included mainly qualitative questions which were designed to examine students’ understanding of the functional relationships between the variables in an electric circuit. The main findings obtained from the analysis of the responses are current is the primary concept used by students, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
26

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(169 citation statements)
references
References 0 publications
4
129
0
26
Order By: Relevance
“…Examples of fundamental student misconceptions that have been observed include that: current is consumed in circuits [9], current divides into two equal parts at all circuit junctions [10], batteries maintain a fixed current regardless of load [11], batteries in parallel provide more voltage [12], and students have problems identifying the important topological aspects of circuits [13]. In addition to qualitative misconceptions regarding the behavior of DC resistive electric circuits, students often make quantitative circuit analysis mistakes, including: incorrectly labeling voltage polarities and current directions, simplifying circuits incorrectly, formulating and solving node voltage equations incorrectly, formulating and solving mesh currents incorrectly, and applying and solving via superposition incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of fundamental student misconceptions that have been observed include that: current is consumed in circuits [9], current divides into two equal parts at all circuit junctions [10], batteries maintain a fixed current regardless of load [11], batteries in parallel provide more voltage [12], and students have problems identifying the important topological aspects of circuits [13]. In addition to qualitative misconceptions regarding the behavior of DC resistive electric circuits, students often make quantitative circuit analysis mistakes, including: incorrectly labeling voltage polarities and current directions, simplifying circuits incorrectly, formulating and solving node voltage equations incorrectly, formulating and solving mesh currents incorrectly, and applying and solving via superposition incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…However, students often focus only on the local effects, and tend to neglect the global effects of dynamic processes [1]. For example, Cohen et al [45] found that when students were asked what happens when one part of an electric circuit was altered, 27% of students considered only the local effects of the change and did not think about global changes to the whole circuit. Within the domain of metabolic pathways, explaining the control properties of networks of coupled enzyme-catalyzed reactions in steady state requires systems thinking and a theoretical framework such as metabolic control analysis (e.g.…”
Section: Reason Locally and Globally About The Concept (System Thinking)mentioning
confidence: 99%
“…(Chu & Lee, 2005;Cohen et al, 1983;Heller & Fineley, 1992;Kim et al, 1990;Küçüközer & Demirci, 2008;Moon & Kwon, 1991;Pardhan & Bano, 2001). The magnitude of the current in the electric circuit with one battery is larger than that in the electric circuit with two batteries in series connection.…”
Section: Learned Conceptmentioning
confidence: 99%